Changing family - changing solidarity? : The phenomenon of family solidarity - Takács, Erzsébet (Szociológiai Szemle, 2023)
The pluralisation of family forms significantly influences several aspects of family solidarity and the solidarity between generations. Its analysis is made difficult by its complexity: while values research into consensual and normative solidarity as well as the literature on the subject, deal with changes of emotional solidarity predominantly within theoretical frameworks, social and functional solidarity are examined through generational transfers. This paper attempts to provide an overview of the Hungarian conditions along the six interpretative dimensions elaborated by Vern L. Bengtson and Petrice S. Oyama with the help of earlier Hungarian empirical findings. The paper does not offer new empirical results; its primary achievement is being to first to approach the phenomenon of family solidarity with all its ramifications in Hungary in an interdisciplinary context. The paper also attempts to reflect upon the fact that while family solidarity is undoubtedly a positive phenomenon at the level of the individual as well as that of the family (due to its role in protecting the self, identity, and supporting existential security), from a social point of view family and generational solidarity is a significant and increasingly dominant factor in regenerating social inequalities.